KETERSEDIAN TENAGA KERJA SEKTOR PERTANIAN DI DAERAH PENYANGGA TAMAN NASIONAL GUNUNG GEDE PANGRANGO (Agricultures Labour Availability in the Bufferzone of Gunung Gede Pangrango National Park) - Sambas Basuni; Tatang Kurniawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
Ability of buffer zone in protecting conservation area depends very much on development of economic opportunity of the buffer zone area itself. The objective of this research was to provide description on economic condition of the buffer zone of Gunung Gede – Pangrango National Park (TNGP) based on economic indicators, particularly the availability of labor in agriculture sector. Method of Location Quotient (LQ) was applied to describe whether the agriculture labor in buffer zone constituted the base sector or not. Employment Surplus Index (ESI) was used to calculate surplus of agriculture labor while Shift Share Analysis (SSA) was used to show shift in labor availability in agriculture sector. Research results showed that agriculture sector labor in buffer zone of TNGP constituted the base sector and implied that agriculture sector possessed extra labor. In general, villages in buffer zone of TNGP showed very dynamic shift of labor availability in agriculture sector. Excess labors were considered as labors that serve export market. Considering that ratio of agriculture land size to number of inhabitants in buffer zone of TNGP was very small, accompanied by low level of education and skill of the inhabitants whose livelihood was limited on skill based on land and natural resources, it can be predicted that export of excess labors in buffer zone villages will go to TNGP area in the form of forest area disturbance. Therefore, one of the attempts to overcome the problem of agriculture labor surplus was seeking potency and development of farmer ability in non agriculture job.